Local trends in older people presenting at an emergency department. Issue 4 (August 2017) - Halcomb, Elizabeth; Smyth, Elizabeth; Ghosh, Abhijeet
Abstract: Background: Emergency Departments are increasingly reporting difficulties in managing their patient load within the available resources. Older people contribute significantly to the number of presentations seen in Emergency Departments. Understanding the nature of presentations can help to appreciate how they might be best managed to assist in effective resource utilisation and patient care. Aim: This study aimed to explore presentations to an outer metropolitan Emergency Department by older people. Design: Retrospective review of all Emergency Department presentations of individuals aged over 65 years. Participants: 8469 older individuals who presented to an outer metropolitan Emergency Department between July 2013 and September 2014. Methods: Medical record data items included demographics, triage category, presenting problem(s), disposition and length of stay. Findings: 14, 976 Emergency Department presentations were made by 8469 older people. High attenders (n = 405 older individuals) accounted for 18.7% (n = 2798) of the total presentations. Almost half of the presentations (48.9%) were triaged as Category 3 presentations, with a further 29% triaged as Category 4. Whilst overall the most frequent discharge diagnoses were chest pain (3.8%), fall (3.0%) or COPD (2.9%), for the high attenders the most frequent discharge diagnoses were COPD (6.4%), chest pain (4.0%) and fall (3.1%). Only 54.2% (n = 8124) of all presentations led to a hospital admission. Conclusion: Our data demonstrated that a proportion of presentations to the Emergency Department by older people could be reduced as many individuals did not require hospital admission. This would alleviate burden on the Emergency Department and potentially improve continuity of care and outcomes. Further research needs to explore the reasons that older people present to Emergency Departments rather than using other services and explore how primary care services can better meet these health needs. Additionally, educational strategies need to be implemented to improve consumer decision making about which health services they access and empower consumers to better manage their health.